REMOVAL OF IRON AND MANGANESE BY NANOFILTRATION PILOT SYSTEM - Zat, Michely; Konrad, Odorico; Strotmann, Uwe; Bezama, Alberto; Lumi, Marluce (Revista de Estudos Ambientais, 2014)
By human activities numerous organic and inorganic pollutants and nutrients such as nitrogen and phosphor containing compounds have been discharged into water causing widespread contamination problems. Ionic compounds such as iron (Fe2+) and manganese (Mn2+) are frequently found in discharges of pollutants.Â Therefore, they may deteriorate the organoleptic characteristics of drinking water, causing taste, color and odor. These compounds are not completely removed by conventional water treatment plant processes and remain in the water. Thus this study was performed to evaluate the efficiency of a nanofiltration process with respect to the removal of iron and manganese. The nanofiltration system proved to be very efficient and could effectively increase the water quality.